Climate change impacts on rice (Oryza sativa) productivity and strategies for its sustainable management - KINGRA, P K; KAUR, RAMANJIT; KAUR, SATINDER (The Indian Journal of Agricultural Sciences, 2019)
Increase in climatic variations and extreme weather events in the recent past have exerted significant effect on crop productivity over different regions on earth. Such aberrations and their adverse effect on agriculture cannot be overruled in the years to come, rather it is expected to increase in future, which necessitates the need to understand their impact on crop productivity so that viable management options can be explored to sustain crop productivity and food security in future. Rice (Oryza sativa L.) is the most important staple food for about 150 million people worldwide, especially in east and south Asia, the middle east, Latin America and the West Indies. It is a tropical crop and is thus adapted to warm and humid conditions. Tropical and sub-tropical areas are at, a greater risk as the prevailing temperatures are already on higher side in these areas and the crops are therefore exposed to warmer limits. Thus, in warm areas of the world, future global warming may result in substantial yield decrease because of the sensitivity of flowering and seed set to high temperatures and the possibility of water shortage that may result from increased evapotranspiration. Warming conditions may lead to reduction in crop duration and increase in respiratory losses, thus decreasing net photosynthesis and crop productivity. Although increase in CO2 levels lead to positive growth response, this effect is nullified due to increase in temperature. Increase in CO2 concentration can counterbalance the effect of increase in temperature by 1–2oC but further warming will have negative impact on rice productivity even under elevated CO2 levels. To overcome the adverse effects of climate change on rice productivity, agronomic management practices like cultivation system, irrigation management and fertilizer management etc. can play a significant role either by leading to reduction in greenhouse gas (GHG) emission or by reduction of climate change impact on rice productivity. In addition to this, various breeding techniques like screening for stress tolerance, conventional breeding techniques as well as molecular and biotechnological strategies need to be incorporated for developing varieties tolerant to various stresses.